The impact of transformational and transactional leadership styles on job satisfaction among employees at Economic Planning Unit, Prime Minister Office Putrajaya / Noor Hidayah Sulaiman - Sulaiman, Noor Hidayah (Faculty of Business and Management, 2018)
This study was conducted at Economic Planning Unit, Prime Minister Office, Putrajaya. The objective of this study is to find out which leadership styles the employees more prefer either Transactional leadership styles or Transformational leadership styles. Questionnaire were gives to 60 respondents to complete this survey. Data were analyzing by using SPSS and the result of the study will be used for the company in the future and they can know about leadership style that the choose. The major finding for this research is can identify which leadership styles that have a relationship on job satisfaction among employees and which leadership styles is most significant in the organization. Leadership is important in all organization because leader will guide the employees to achieve the company goals and also motivate and encourage employees to move and think forward.